PhaF, a Polyhydroxyalkanoate-Granule-Associated Protein of Pseudomonas oleovorans GPo1 Involved in the Regulatory Expression System for pha Genes - Prieto, Maria A. (American Society for Microbiology, 1999)
The phaC1 gene codes for the medium-chain-length polyhydroxyalkanoate (mcl PHA) synthase of Pseudomonas oleovorans GPo1, which produces mcl PHA when grown in an excess of carbon source and under nitrogen limitation. In this work, we have demonstrated, by constructing a recombinant P. oleovorans strain carrying a phaC1::lacZ reporter system, that the phaC1 gene is expressed efficiently in the presence of octanoic acid while its expression is repressed when glucose or citrate is used as the carbon source. Moreover, a P. oleovorans GPo1 mutant (strain GPG-Tc6) expressing higher levels of the reporter gene than the wild-type strain in the presence of glucose or citrate has been generated by mini-Tn5 insertional mutagenesis. Characterization of this mutant allowed us to conclude that phaF, a gene located downstream of the pha gene cluster, was knocked out in this strain. P. oleovorans GPG-Tc6 regained the ability to control phaC1 gene expression when complemented with the phaF wild-type gene. Sequencing data revealed the presence of three complete open reading frames (ORFs) in this region: ORF1 and phaI and phaF genes. The amino acid sequences of the phaI gene product and the N-terminal half of the PhaF protein showed a significant degree of similarity. Furthermore, the primary structure of the PhaF C terminus identifies this protein as a member of the histone H1-like group of proteins. Northern blot analysis showed two transcription units containing phaF, i.e., phaF and phaIF transcripts. Expression of the phaIF operon is more efficient in the presence of octanoic acid and is enhanced by the lack of the PhaF protein. In addition, it has also been demonstrated that both PhaF and PhaI proteins are bound to PHA granules produced by P. oleovorans. A model for the role of PhaF in regulating PHA synthesis is presented.